An Analysis of Poverty and Inequality among Indigenous Nationalities of Nepal - Lama, Nabraj (International Journal of Humanities and Social Science Research, 2019)
Indigenous nationalities are among the poor and deprived communities around the globe, and it follows the same pattern in Nepal, but the poverty level of each ethnic population within the broader category of indigenous nationalities are not homogenous. This paper has calculated and analyzed the poverty status of each ethnic community within indigenous nationalities. The study is based on the raw data of Nepal Social Inclusion Survey, Social Inclusion Atlas-Ethnographic Profile project conducted by the then Central Department of Sociology/Anthropology, Tribhuvan University, and Nepal Living Standard Survey – III. The study shows that the ten poorest groups have a poverty rate of more than double the national average whereas the ten affluent groups have poverty rate below the national average. The finding indicates the existence of strong inter-ethnic economic inequality. Thus, the benefits and opportunities to the indigenous nationalities should be prioritized based on the financial status of each ethnic community rather than considering them in a single homogenous basket.